Information disclosure, practical actions and dynamics of employees' health and safety issues in Chinese family businesses—Evidence based on Chinese a-share listed companies - Guo, Yi; Li, Aijun; Zhou, Yi; Di, Yuna (Frontiers in Public Health, 2022)
Introduction Global health emergency as COVID-19 has brought unprecedented concerns to the health and safety of employees, which is important yet long-neglected. This paper studies the mechanism and influencing factors of Chinese family enterprises performance in employees' health and safety from information disclosure, practical action and dynamic change. And based on theoretical framework and empirical model, this paper provides feasible regulatory policies on the behavior of family business. Methods This study construct a game theory framework and uses a sample of Chinese A-share listed companies. The database is provided by a third-party corporate social responsibility rating agency, SynTao Green Finance. We use empirical models to test the hypothesis from the theoretical model of game theory. Results In practice, family businesses are less likely to fulfill the health and safety responsibilities of employees compared to non-family businesses. Family businesses are likely to be more motivated than other businesses to send signals that they are performing their responsibilities well. From the view of operation term, family businesses will be gradually inclined to better fulfill the health and safety responsibilities of their employees, while this process will show a “U” shape change over operation time. Conclusions As there is inconsistency between the information disclosure and actual practice of family enterprises when it comes to the issue of employee health and safety, more related regulatory policies and stakeholder monitoring are needed. Although the performance of family enterprises in this regard will be better in the long run, it is still necessary to improve employees' legal and rights awareness and enhance the effectiveness of supervision over external stakeholders.